Theoretical Review of the Subjects and Objects of Income Tax and Value Added Tax in Indonesia - Junius Piter Kalumbang; Regina Jansen Arsjah (Utan Kayu Publishing, 2025)
The tax system is the main pillar of state financing as well as an instrument for creating social justice and sustainable economic development. This study aims to examine in depth the concept of tax subjects and objects in Income Tax (PPh) and Value Added Tax (PPN), and to compare the fundamental differences between the two in terms of regulation, implementation, and contribution to state revenue. Using a descriptive qualitative approach through literature study and content analysis, this study synthesizes data from laws and regulations, scientific journals, and official institutional reports. The results of the study show that PPh focuses on income received by individuals or corporate entities, while VAT is imposed on the consumption of goods and services without distinguishing between consumers. The PPh collection system is direct, while VAT is indirect through business actors. Although it adheres to the principle of self-assessment, the implementation of the tax system still faces challenges in the form of low tax literacy and voluntary compliance. In addition, the development of the digital economy, cross-border transactions, and tax avoidance practices require regulatory adaptation and strengthening of supervision. This study emphasizes the importance of synchronizing tax theory, fiscal policy, and administrative capacity to respond to global dynamics. The main contribution lies in the development of a subject- and object-based tax analysis framework and policy implications for the government, academics, and business actors in designing a fair, efficient, and sustainable taxation system.